Tuburan Coffee Farmers: its Impact on Regional Eco-Tourism - Galagar, Monifel S; Gabuya, Jr, Alden Q (Journal of Business on Hospitality and Tourism, 2022)
Rural tourism has been widely encouraged, promoted and relied on as a useful means of tackling the social and economic challenges faced by those rural areas associated with the decline of traditional agrarian. This study aimed to analyses the importance of local agricultural flora in the promotion of Tourism in Tuburan, Cebu.The study used the ethnography method that identified the agricultural resources found in Tuburan, Cebu. Furthermore, it also identified the benefits of a community’s local resources in the promotion of tourism as well as the challenges encountered which hinder the growth of tourism. The study was conducted in Tuburan, Cebu. There were 20 informants who were chosen through judgmental sampling to provide their personal experiences as to their visit of the place. Simple percentage was used to summarize, analyze and interpret the data. The findings revealed that coffee, banana, cacao, coconut, and corn are the major agricultural floras in Tuburan, Cebu and coffee was found to have the biggest land area among all the other major floras giving a distinct identity of the municipality, thus coffee has been the motivating factor of the tourist in visiting Tuburan. It was also found that agricultural floras are greatly beneficial to the community and its people by opening job opportunities, empowering the people, building social relationships, and uplifting people’s morale. Lastly, the major challenges encountered by the informants in visiting and promoting tourism are poor facilities and services in the coffee farms, transportation, communication and manpower.